Understanding the Behavior of Domestic Emus: A Means to Improve Their Management and Welfare—Major Behaviors and Activity Time Budgets of Adult Emus. (5th November 2014) - Menon, Deepa G.; Bennett, Darin C.; Cheng, Kimberly M.
Abstract : Information on domestic emu behavior is sparse and hence a study was undertaken to identify and describe the behavior of domestic emus in a farm setting. The behavioral repertoires, activity time budgets, effect of time of the day, sex, weather, and relative humidity on activities of adult emus were investigated. Eight randomly selected emus were observed using one-zero sampling method for 12 days, each period of observation lasting 30 minutes. The major behavioral categories identified were ingestive drinking, standing, locomotion, grooming, socialization, vocalization, and resting. The emus spent most of their time walking, standing, and eating. Immediately after moving to a new pen, emus were found to huddle together to keep away from emus already resident in the pen. The time spent on each activity was not significantly different between the sexes. The findings from this study provided important information on the behavior and activities of emus. The observed behaviors need to be further examined to assess their relations to the birds' welfare.